Über einigen Geometrischen Objekten des metrischen Linienelementraumes - V. Bliznikas, (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Близникас. О некоторых геометрических объектах метрического пространства линейных элементовV. Bliznikas. Apie kai kuriuos metrinės tiesinių elementų erdvės geometrinius objektus